Discovery of Single Nucleotide Polymorphisms for Resistance to Abnormal Vertical Growth in Macadamia - Zakeel, Mohamed Cassim Mohamed; Alam, Mobashwer; Geering, Andrew D. W.; Topp, Bruce; Akinsanmi, Olufemi A. (Frontiers in Plant Science, 2021)
Abnormal vertical growth (AVG) syndrome is a serious threat to the Australian macadamia industry as it decreases the yield of nuts by as much as 70% per annum. A lack of information on the cause of AVG has hindered the development of an effective disease management strategy. Discovery of genetic markers associated with disease resistance can be used as tool for rapid selection of elite cultivars, hence helps in efficient disease management. Differences in field susceptibility of macadamia cultivars provide an opportunity for discovery of genetic markers that are associated with host resistance. REML mixed model analysis was performed to estimate the AVG rating of 51 cultivars from multiple origins using phenotypic data from 359 trees planted in four sites. Most of the Hawaiian cultivars were found as susceptible, while selections from the Australian macadamia industry breeding program were predominantly resistant. All the cultivars were genotyped for 13,221 DArTseq-based single nucleotide polymorphism (SNP) markers. A bulked sample analysis was performed using 20 genotypes each at the extremes of AVG phenotypic ratings. Ten SNP markers were predicted to be associated with AVG resistance and two arbitrarily selected SNP markers were validated using PCR and Sanger sequencing. Our findings suggest that AVG resistance in the commercial cultivars may be derived from the genomic introgression of Macadamia tetraphylla through interspecific hybridization. The results may support marker-assisted selection for macadamia germplasm with AVG resistance.